3D printable and fringe electric field adhesion enabled variable stiffness artificial muscles for semi-active vibration attenuation. Issue 28 (16th June 2021) - Liu, Chen; Li, Bo; Li, Zhuoyuan; Cao, Chongjing; Gao, Xing; Zhang, Ketao; Chen, Hualing
Abstract : A light and fully flexible artificial muscle fabricated by 3D printing is able to instantly promote its stiffness by an induced fringe electric field with different voltages, which is then implemented as a semi-active absorber for vibration attenuation. Abstract : Soft robots are able to generate large and compliant deformation in an unconstructed environment, but their operation capability is limited by low stiffness. Thus, developing the function of variable stiffness while preserving its compliance is a challenging issue. This study proposes a new variable stiffness artificial muscle, as a complementary component for soft robots, using the principle of fringe electric field adhesion. Taking inspiration from the mechanism of multi-layer structures in biological muscles, the artificial muscle is composed of patterned conductive layers and interlayers and is 3D printable by direct ink writing (DIW). To further demonstrate the application, a vibration absorber by stacking this artificial muscle is proposed, whose natural frequency is tunable by the varying stiffness. The advantages of the fringe electric field-enabled variable stiffness (FEVS) artificial muscles include lightweight and irrelevance of the stiffness to the thickness of the interlayer, which can be beneficial to soft robots to achieve variable stiffness and semi-active vibration attenuation without extra weighting load.